NEW METHODS FOR SPECIFICATION LATENT LOSSES FOR ELECTRICITY TRANSMISSION BY OVERHEAD LINES - Ľuboš PAVLOV; Ľuboš SKURČÁK (Acta Electrotechnica et Informatica, 2019)
The submitted contribution is devoted to the issue of the existence of latent losses on the overhead lines. Quantification of latent losses of electricity is a very complicated task, which has been solved in practice for several years. In their assessment, however, often appear some inconsistencies which cause is often unknown. The magnitude of these losses in some cases cannot be negligible. From the point of view of maintaining an efficient and reliable operation of distribution and transmission systems in the future, attention will still need to be paid to the problem of latent loss analysis.